Intestinal lymphoid nodular hyperplasia in children: The relationship to food allergy. Issue 1 (February 2015) - Lucarelli, Sandra; Lastrucci, Ginevra; Di Nardo, Giovanni; D'Alfonso, Ylenia; Aloi, Marina; Oliva, Salvatore; Frediani, Simone; Rossetti, Danilo; Frediani, Tullio
Abstract Background Lymphoid nodular hyperplasia (LNH) of the lower gastrointestinal tract is a common finding during paediatric colonoscopies, and its clinical significance has not yet been clearly established. Objective The purpose of this prospective, parallel multi‐arm, randomized clinical trial was to study relationship between food allergy and LNH. Methods We recruited 268 children who had undergone a diagnostic colonoscopy between 1 January 2009 and 30 September 2011. The inclusion criteria were the following: (i) demonstration of LNH; (ii) no concomitant inflammatory or immune disease; (iii) no treatment since the clinical onset. The patients were assigned 1:1:1 to elimination diet (Group A), mesalamine (Group B) or symptomatic treatment with antispasmodics or antidiarrhoeal drugs (Group C) for an 8‐wk period. Patients were followed for 24 months. Results We enrolled 72 of 97 children with intestinal LNH who were referred for haematochezia (76%), recurrent abdominal pain (68%) and/or chronic diarrhoea (32%). Clinical improvement was observed in 75%, 83% and 79% of the patients in Groups A, B and C, respectively. The difference in the response to treatment among the groups and the association to the clinical, endoscopic and allergic features of the patients were not statistically significant. Conclusions Intestinal LNH should be considered a benign finding in children without red flags, because the symptoms are largely self‐limiting. The use of mesalamine or elimination diet does not modify the clinical outcome compared to symptomatic therapy. The presence of food allergy was not predicted by allergy skin testing and was found in a minority of patients.